ANALISIS KECACATAN PRODUK PADA PRODUKSI BATU BATA MERAH DENGAN METODE PLAN, DO, CHECK, ACT PADA DR GROUP MAJENANG - Rusyd, Ibnu (nter of Execellence (COE) ICT Infrastructure, Smart Manufacture and Digital Supply Chain, 2022)
DR Group Majenang is an MSME engaged in printing production. One of the products produced is red brick. In January 2022, DR Majenang Group can produce 15,500 red bricks but 840 red bricks fail or are considered defective. There are 2 (two) types of products that occur in red bricks, namely slow drying and brudul. Slow drying defects in January 2022 reached 445 pieces (53%), while the delivery of fruit was 395 pieces (47%). For this purpose, this research was conducted with the aim of knowing the causes of rejection of red brick products and proposed improvements using the PDCA (Plan, Do, Check, Action) method and the tools used are: Pareto diagrams, Fishbone diagrams, p-charts. The result of the research is the cause of the occurrence, namely the soil material that is not in accordance with the standard for the completion of the purchase of soil material with the quality of the soil which is dark red in color and when clenched by hand it clumps. The soil that is said to be not good is soil that is a bit dark black and if it is clenched it will not clump. The absence of supervision is the supervisor of every production process taking place and the use of a 6:2,5 measure. Six (6) for soil and two and a half (2.5) for water with a cast bucket measuring 31x26 cm, but the employee was negligent and gave a dose of 3 buckets or even more.